Essentials of general surgery - 4 0 16; Lawrence, Peter F.;Bell, Richard M.;Dayton, Merril T.; 5 (Philadelphia : Lippincott Williams & Wilkins, 2000)
A textbook for medical students that provides an introduction to the fundamentals of general surgery, with review questions, diagrams, and photographs.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Surgery.;Surgical Procedures, Operative.;Surgery.; 20; 2